Edukasi Pencegahan Gangguan Otot Rangka Akibat Kerja pada Petani di Kabupaten Deli Serdang Tahun 2022 - Sumihar Pasaribu; Septa Dwi Insani; Fahrizal Alwi (LLPM Universitas Deli Sumatera, 2024)
Musculoskeletal disorders are discomfort caused by injury to muscles, tendons, joints, nerves, and soft tissues while working. Musculoskeletal disorders are conditions of discomfort or pain caused by injury and disorders of muscles, tendons, joints, nerves, and other soft tissues while working. Working conditions that often involve activities such as lifting, carrying, pulling, pushing, and repetitive movements during work, uncomfortable or static positions, using excessive force to complete tasks, being exposed to excessive vibration, or working in extreme temperatures, and doing high-speed rolling work can all increase the risk of musculoskeletal complaints. Musculoskeletal complaints can be prevented by doing stretching exercises. Providing stretching exercises to workers can have a significant impact on reducing musculoskeletal complaints. By exercising regularly at least 4 times a week with a duration of 5 to 10 minutes, the joint range of motion will become wider